Characteristics for Performance Optimization of Safety-Critical System Development (SCSD) - Ahmed Thawaba, Abdulaziz; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Wadata, Junzo (J-STAGE, 2020)
Safety-critical systems (SCS) are the most significant systems that affect our daily life in many areas such as flight control systems, railway systems, medical devices, nuclear systems, and military weapons. SCS failures could result in losing life or serious injuries. Improving the practices during development phases of SCS can reduce failures up to 40%, thus resulting developers to follows specific development practices and techniques. Developers should improve safety-critical system development (SCSD) by taking into account all factors and understanding the causes of failure. Previous studies have highlighted the causes of failure during the development of SCS, but for specific areas such as designs, requirements, or the human factor, while developers need to know the causes of failure in all areas and the relationship between them clearly and comprehensively. This research aims to analyze SCSD characteristics and discuss performance improvement as well as causes of failure. This paper proposed a guideline that helps developers reduce the causes of failure during SCS development. This guide has four characteristics, each with a role in improving SCSD and reducing causes of failure.